Hypoxie and Hyperoxia - Zinner C; Sperlich B (Dynamic Media Sales Verlag, 2019)
In contrast tothe various acute and chronic responses to hypoxia (i.e., lowering of the partial pressure of oxygen in the air, for example by various forms of altitude training), far less is known about the responses to acute, and especially to chronic exercise in hyperoxia (i.e. elevation of the fractional oxygen content of air). The acute exposure to hyperoxia while exercising improves e.g. oxygen uptake and neural drive and lowers levels of blood lactate and ratings of perceived exertion. Therefore, training in hyperoxia may allow higher exercise intensity, thus imposing a greater physiological training stress. With this systematic review (n=7 studies; years: 1996-2016), we aimed to analyze the medium-term ergogenic properties of hyperoxic vs. normoxic training. Based on the existing datafor cycling and running (3-6 wks with 2 to 5 sessions per week) in hyperoxia (oxygen fraction 0.60-1.00) vs. normoxia, we conclude that hyperoxic training improves performance (Cohens d=1.79) and oxygen uptake (d=0.57) in normoxia to large and medium extents, respectively. Future studies are warranted to investigate the long-term performance and health effects of hyperoxic training for athletes in different disciplines.KEY WORDS: Acclimation, Fatigue, Cycling, Running Oxygen Uptake, Oxygen Partial Pressure, Systematic Review